Creativity as care during COVID19: The domestic pedagogies of learning from home - Trezise, Bryoni (Critical Studies in Teaching and Learning, 2023)
This article reflects upon relationships between pedagogy and domesticity in relation to a creative teaching philosophy of ‘critical care’. Two contexts frame this discussion. The first: the socio- economic levers that, prior to the pandemic, were working hard to reposition creativity as a 21st century skill demanded by employers and commodified in languages of entrepreneurial innovation by Higher Educational institutions. The second: the home-schooling conditions of Sydney’s twin pandemic waves, which for many, merged the homespace and workplace in ways not yet fully understood. In using pedagogy to bridge the logics of homespace and workplace during lockdown, I invoke a series of frameworks invested in expanded notions of creativity. These are performed as ‘intermezzo’: offering intercutting, non-finished evocations of the disrupted and scattered self. The haiku poetry of a group collaboration timestamps modes of paying attention as one pathway that counterpoints the neoliberalisation of creativity with small acts of everyday world-building.